Процеси та організація комутації трифазного трансформатора - Халіков, В.А. (Технічна електродинаміка, 2012)
Transient processes appearing over core saturation on switching of the primary winding of a three-phase transformer are considered. Visual modeling of transient processes is done with MATLAB and techniques for minimization or elimination of transients are suggested.